Declines in suspended sediment concentration and their geomorphological and biological impacts in the Yangtze River Estuary and adjacent sea. (5th February 2022) - Huang, Yuan-Guang; Yang, Hai-Fei; Jia, Jian-Jun; Li, Peng; Zhang, Wen-Xiang; Wang, Ya Ping; Ding, Yi-Fan; Dai, Zhi-Jun; Shi, Ben-Wei; Yang, Shi-Lun
Abstract: Variations in suspended sediment concentrations (SSCs) in coastal areas affect both geomorphology and biological environment. In this study, more than 82, 000 surface-water samples have been collected twice daily at 10 stations in the Yangtze River Estuary and adjacent sea (YRE–AS) between 1990 and 2020 to study how the SSC has varied in response to intense human activities in the Yangtze watershed. Between the periods 1990–1999 and 2000–2020, the annual averaged SSC at the Datong station (the tidal limit in the Yangtze River) decreased by 56% (from 0.36 to 0.16 g/l, p < 0.05), which was mainly owing to sediment retention by dam constructions and the implementation of soil conservation measures in the drainage basin. Meanwhile, the annual averaged SSC in the YRE–AS (10 stations) decreased by only 28% (from 0.56 to 0.40 g/l, p < 0.05), which was markedly smaller than the relative decrease in the SSC at Datong. This phenomenon is primarily because that the sediment resuspension induced by tides and waves can mitigate the influence of the fluvial suspended sediment discharge (SSD) decline on the SSC in the YRE–AS. There is a time lag of 0–12 years between the change in SSD from the Yangtze River and the subsequent response of the SSC levels in the YRE–AS. The time lag increased from 0 to 1 years in the tidal current limit to ∼12 years in the mouth bar area of the YRE, along with the marine force getting stronger and the riverbed sediments getting finer seaward. As the shading effect of suspended sediments in seawater can limit photosynthetically available radiation, the decline in the SSC might affect the growth of phytoplankton in the YRE–AS. Since 2000, the concentration of chlorophyll a (Chl-a) off the YRE–AS has increased by 61.4% (from 3.45 to 5.57 mg/m 3, p < 0.05) and the annual frequency of algal blooms has increased by over 5 times (increased from 6.27 to 31.6, p < 0.05). The decreased SSCs in the YRE–AS and its impacts on the geomorphology and biological environment would aggravate because of increased human activities. Highlights: Mean SSC in the YRE–AS has decreased by 28.5% (decreased from 0.56 to 0.40 g/l, p < 0.05) in the recent 20 years. The decreased SSC in the YRE-AS was attributed to river damming. A time lag of 0–12 years between the SSC in the YRE–AS and the riverine SSC was found. The longest time lag (12 years) in SSC is located in the mouth bar area of the YRE–AS.